Psychological, Physiological, and Physical Effects of Resistance Training and Personalized Diet in Celiac Women - Martínez-Rodríguez, Alejandro; Loaiza-Martínez, Daniela Alejandra; Sánchez-Sánchez, Javier; Rubio-Arias, Jacobo Á.; Alacid, Fernando; Prats-Moya, Soledad; Martínez-Olcina, María; Yáñez-Sepúlveda, Rodrigo; Asencio-Mas, Nuria; Marcos-Pardo, Pablo J. (Frontiers in Nutrition, 2022)
Background: Gluten intolerance is a systemic process of autoimmune nature; it develops in genetically predisposed subjects with gluten ingestion. The only treatment for CD is a lifelong strict gluten-free diet (SGD). This study was designed to assess adherence to a GFD, risk of an eating disorder, measure blood tests and nutritional variables to assess the prevalence of vitamin and mineral deficiencies in adult CD patients undergoing different interventions; Methods: A total of 28 Spanish women, aged 40 years old or more, took part in a randomized controlled tri-al. Each group received a different intervention: group 1, gluten-free nutrition plan + exercise (GFD + E); group 2, gluten-free nutrition plan (GFD); group 3, celiac controls (NO-GFD); and group 4, non-celiac controls (CONTROL). The variables studied were adherence to the gluten-free diet, risk of eating disorders, blood values and body composition. Results: Celiac women with personalized nutritional planning presented greater adherence to a gluten-free diet (p<0.001). Regarding leukocytes, significant differences were observed between the GFD and CONTROL groups (p=0.016). Perimeters and folds did not decrease significantly. Conclusions: Those people with CD who have nutritional planning tailored to their needs have greater adherence to a DMG than those who do not have it planned. This translates into a greater or less-er immune system response (leukocyte levels). An isocaloric GFD plan together with resistance training improves body composition.